Meningkatkan Penghayatan Spiritualitas Kateketis dalam Terang Injil Yohanes 10:1-21 bagi Katekis di Paroki Kristus Raja Wangatoa Keuskupan Larantuka - Yoseph Thomas Suhartono Bungalaleng; Antonius I.N Tukan; Florens Maxi Un Bria (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
sacrifice, compassion, and service to His people. These values form the foundation of the spirituality that every catechist is called to embody in carrying out the mission of evangelization. However, various challenges remain evident in pastoral ministry, including a lack of solidarity, tardiness in ministry activities, low enthusiasm in fulfilling assigned responsibilities, a tendency to speak more than to act, and limited participation in spiritual activities. This study aims to examine catechists' lived spirituality in the light of John 10:1–21, identify the factors that support and hinder its practice, and propose efforts to strengthen it. The research employs a qualitative method using a content analysis approach to analyze the collected data. The theoretical framework discusses the spirituality of catechists, the theological meaning of John 10:1–21, and its relevance to catechetical ministry. The preliminary hypothesis suggests that some catechists have not yet fully understood and internalized their vocation, resulting in a spirituality that requires further development. The findings indicate that, in general, catechists have acquired an adequate understanding of spiritual formation through continuous education and ongoing formation programs. They understand their identity and mission as sharing in Christ's offices of priest, prophet, and king, as well as their role as proclaimers of the Gospel. Nevertheless, the lived practice of this spirituality still requires continuous accompaniment and formation so that it may be more fully reflected in their attitudes, commitment to ministry, and witness in accordance with the example of Jesus, the Good Shepherd.